Reports on the results of the N.Oc. "Prof. W. Besnard" expeditions to the southern coast of Brazil under the Revizee Program: Chirostylidae and Galatheidae (Crustacea: Decapoda: Anomura) - de Melo-Filho, Gustavo A.s. (Zootaxa, 2006)
The distribution patterns of the species of the family Chirostylidae and Galatheidae collected under the Revizee Program (Living Resources in the Exclusive Economic Zone) off the Brazilian southern coast are analyzed. The study area extended from the Cape São Tomé (Rio de Janeiro; 22°00’S) south to Chui (Rio Grande do Sul; 34°30’S). The collections were made during several cruises of N.Oc. “Prof. W. Besnard” between December 1997 and April 1998 over the shelf and slope (60–808 m). One species of the genus Agononida, seven species of the genus Munida, one species of Munidopsis and one of Uroptychus were collected.